PENGARUH PLATFORM E-COMMERCE TERHADAP PERILAKU PEMBELIAN KOMPULSIF PADA IBU RUMAH TANGGA DI KABUPATEN SIDENRENG RAPPANG - Ansari Abdillah; Mau, Muliadi; Sonni, Alem Febri (Nusantara Hasana Journal, 2025)
The development of technology has been a major factor behind the growth of e-commerce. The future of e-commerce in Indonesia is promising, with an estimated annual growth rate of 53.23%. By using e-commerce platforms, people can easily search for and select the products they wish to purchase. This convenience makes shopping a favored activity, not only for fulfilling needs and desires but also for influencing compulsive buying behavior. This study was conducted using a quantitative descriptive research methodology. This approach is useful for identifying relationships between two or more variables. The correlation analysis test results show that the calculated t-value is 8.064 with a p-value of <0.05. These research findings indicate that e-commerce platforms significantly influence compulsive buying behavior among housewives in Sidenreng Rappang Regency. The study relies on self-reported data, which may be subject to social desirability bias or inaccurate recall by participants. This study provides empirical evidence on how e-commerce platforms influence compulsive buying behavior, particularly among housewives in Sidenreng Rappang Regency.